Leopoli-Cencelle (9th-15th centuries CE), a centre of Papal foundation: bioarchaeological analysis of the skeletal remains of its inhabitants - Marica Baldoni; Francesca Romana Stasolla; Giuseppina Scano; Luigi Tonino Marsella; Olga Rickards; Cristina Martínez-Labarga (Taylor & Francis Group, 2020)
Background The medieval city of Leopoli-Cencelle (9th-15th centuries CE) represents an exceptional study-model for extending our knowledge of the Italian Medieval period due not only to the large sample size available but also to the widespread presence of material data and a well preserved archaeological context. Aim This research aims to reconstruct the osteobiography of the inhabitants of this centre of Papal foundation. Subjects and methods The analysed sample counts 877 individuals. Scientifically established anthropological morphological methods were used for assessing their biological profile as well as for reconstructing lifestyle and health status. Results The sample consists of 62.49% adults and 37.51% non-adults. The mortality pattern shows the highest peak prior to 1 year and between 1 and 6 years of age and a reduced longevity of female individuals as commonly observed in pre-antibiotic era populations. Metric and musculoskeletal stress markers revealed different biomechanical stress between sexes probably carrying out different working activities. The palaeopathological analysis supports a general good health status with the exception of a few specific cases. Conclusions The present research helps shed light on the lifestyle of the inhabitants of Leopoli-Cencelle, enhancing a better understanding of the Italian Middle Ages.